Comparison of body fat content and distribution of familial amyloidotic polyneuropathy patients versus healthy subjects - Pimenta, Nuno (2009)
The deposition of amyloid fibers at the peripheral nervous system can induce motor neuropathy in Familial Amiloidotic Polyneuropethy (FAP) patients. This produces progressive reductions in functional capacity. The only treatment for FAP is a liver transplant, followed by aggressive medication that can affect patients' metabolism. To our knowledge, there are no data on body fat distribution or comparison between healthy and FAP subjects, which may be important for clinical assessment and management of this disease.